2009
DOI: 10.1111/j.1439-0531.2008.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Sperm Interaction with Oviductal Epithelial Cells of Llama

Abstract: Sperm reservoirs in South American Camelids would be crucial for successful fertilization. Since ovulation occurs approximately 36 h after mating, the maintenance of the sperm viability in the oviduct waiting for the ovum is a critical reproductive event. Our study aimed at determining whether the isthmus or the utero tubal junction (UTJ) could function as a sperm reservoir in llama by means of in vivo and in vitro experiments. For the in vivo experiments, the oviducts of adult females with a dominant follicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…1995b; Apichela et al. 2009). Strategies underlying sperm binding have been considered, especially in terms of preovulatory sperm storage and suppression of full membranous maturation (Hunter 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1995b; Apichela et al. 2009). Strategies underlying sperm binding have been considered, especially in terms of preovulatory sperm storage and suppression of full membranous maturation (Hunter 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm are held in the reservoir by being bound to oviductal epithelium. In vitro, binding to the oviductal epithelium has been shown to prolong the motile lifespan of sperm of several species [6,[8][9][10][11][12]. Release of sperm from the reservoir is gradual, which helps to reduce the risk of polyspermy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that the llama sperm reservoir is formed at the utero-tubal junction by means of a lectin-like molecule that mediates sperm recognition of N-acetylgalactosamine (GalNAc) and galactose in the female oviduct (Apichela et al, 2010). Under normal conditions, sperm remain attached to the llama utero-tubal junction at least 28 hr after mating (Apichela, Jiménez-Díaz, Roldán-Olarte, Valz-Gianinet, & Miceli, 2009); surgical removal of the bulbourethral glands diminished such sperm attachment (Apichela et al, 2014). The current study sought to isolate and identify the GalNAc-binding lectins present on llama sperm, and to test the hypothesis that they are provided by seminal plasma.…”
Section: Introductionmentioning
confidence: 99%